2000
DOI: 10.1073/pnas.97.1.365
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of α-galactosidase A reduces tissue globotriaosylceramide storage in patients with Fabry disease

Abstract: Fabry disease is a lysosomal storage disorder caused by a deficiency of the lysosomal enzyme ␣-galactosidase A (␣-gal A). This enzymatic defect results in the accumulation of the glycosphingolipid globotriaosylceramide (Gb 3; also referred to as ceramidetrihexoside) throughout the body. To investigate the effects of purified ␣-gal A, 10 patients with Fabry disease received a single i.v. infusion of one of five escalating dose levels of the enzyme. The objectives of this study were: (i) to evaluate the safety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
222
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(228 citation statements)
references
References 29 publications
2
222
1
3
Order By: Relevance
“…The heart is a major target of FD, and its involvement strongly influences life expectancy that was reduced, before ERT introduction, to 58.2 years for men and to 75.4 years for women 21. The impact of ERT on FDCM is still controversial because some studies show benefits from ERT administration in terms of relief,8, 9, 10 and others deny benefits, reporting an unaffected progressive trend 11, 12. Most experts agree on evidence showing that early ERT administration, particularly in prehypertrophic FDCM (MWT <11 mm), prevents disease progression, whereas the advanced form (MWT >15 mm) appears to be irreversible 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heart is a major target of FD, and its involvement strongly influences life expectancy that was reduced, before ERT introduction, to 58.2 years for men and to 75.4 years for women 21. The impact of ERT on FDCM is still controversial because some studies show benefits from ERT administration in terms of relief,8, 9, 10 and others deny benefits, reporting an unaffected progressive trend 11, 12. Most experts agree on evidence showing that early ERT administration, particularly in prehypertrophic FDCM (MWT <11 mm), prevents disease progression, whereas the advanced form (MWT >15 mm) appears to be irreversible 12.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the impact of enzyme replacement therapy (ERT) on FDCM is still controversial,8, 9, 10, 11, 12 and although there is agreement that early ERT administration, particularly in prehypertrophic FDCM, prevents progression of the disease, the advanced form is believed to be irreversible.…”
Section: Introductionmentioning
confidence: 99%
“…Both plasma and urine samples were analyzed with high-performance liquid chromatography using a validated assay, as described previously. 16 …”
Section: Measurement Of Gb 3 Concentrationmentioning
confidence: 99%
“…The level of GL-3 is used as a surrogate marker to assess treatment efficacy, and clearance of GL-3 from the tissues, mainly the liver and kidneys, has been used in several studies as an outcome measure (reported as relative to normal and/or percentage decrease from baseline) (Eng et al 2001;Schiffmann et al 2000). Short-term therapy has been shown to rapidly decrease plasma GL-3 levels in adult and pediatric male patients with FD (Clarke et al 2007;Schiffmann et al 2010).…”
Section: Introductionmentioning
confidence: 99%